The efficacy and safety of urethral injection therapy for urinary incontinence in women: a systematic review (Clinics, 2016)
To evaluate the efficacy and safety of different bulking agents for treating urinary incontinence in women, a systematic review including only randomized controlled trials was performed. The subjects were women with urinary incontinence. The primary outcomes were clinical and urodynamic parameters. The results were presented as a weighted mean difference for non-continuous variables and as relative risk for continuous variables, both with 95% confidence intervals. Initially, 942 studies were identified. However, only fourteen eligible trials fulfilled the prerequisites. Altogether, the review included 1814 patients in trials of eight different types of bulking agents, and all studies were described and analyzed. The measured outcomes were evaluated using a large variety of instruments. The most common complications of the bulking agents were urinary retention and urinary tract infection. Additionally, there were certain major complications, such as one case of death after use of autologous fat. However, the lack of adequate studies, the heterogeneous populations studied, the wide variety of materials used and the lack of long-term follow-up limit guidance of practice. To determine which substance is the most suitable, there is a need for more randomized clinical trials that compare existing bulking agents based on standardized clinical outcomes.